Enhancing the Efficiency of DSSCs by the Modification of TiO2 Photoanodes using N, F and S, co-doped Graphene Quantum Dots. (10th July 2017) - Kundu, Sumana; Sarojinijeeva, P.; Karthick, R.; Anantharaj, G.; Saritha, G.; Bera, Rajesh; Anandan, S.; Patra, Amitava; Ragupathy, P.; Selvaraj, M.; Jeyakumar, D.; Pillai, K. Vijayamohanan
Abstract: We report an enhanced power conversion efficiency (PCE) of 11.7% ± 0.2 and a fill factor (FF) of 71% for dye-sensitized solar cells (DSSC) with an active area of 0.16 cm 2 after modifying the TiO2 photoanode with size-selective (ca. 2 nm) N, F, S-codoped graphene quantum dots (NFS-GQDs) that exhibit a photoluminescence quantum yield (PLQY) of 70%. An upward shift in the Fermi level has been observed, perhaps responsible for the improved performance along with the possibility of preventing the back electron transfer from TiO2 . Mott Schottky analysis indicates a shift (52 mV)in the flat band potential, which is directly related to the Voc of the system. Detailed characterization (IPCE, TCSPC etc) indicates the important role of hetero atoms in facilitating the enhanced performance. Thus, our results suggest that the incorporation of size controlled, hetero atom doped GQDs can enhance the efficiency of DSSCs enabling more opto-electronic applications.